PRAGMATICS DEIXIS ON TAYLOR SWIFT’S SPEECH AT NEW YORK UNIVERSITY - Nisa, Siti Hayatun; Rohbiah, Tatu Siti; Asari, Asari (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study analyzed the types of deixis, references of deixis, and factors influencing the use of deixis in Taylor Swift’s speech at New York University. The research employed Stephen C. Levinson’s theory and utilized a descriptive qualitative method with a content analysis approach. The findings revealed that the data were classified into five types of deixis: personal, spatial, temporal, discourse, and social deixis. The researcher identified 488 instances of deixis, with 277 (61.8%) instances of personal deixis, 37 (8.3%) instances of spatial deixis, 26 (5.8%) instances of temporal deixis, 85 (19%) instances of discourse deixis, and 23 (5.1%) instances of social deixis. It was observed that the dominant reference of deixis was personal deixis. The results indicated that each type of deixis has different references based on the context of its use in the speech. The factors influencing the use of deixis in the speech were social distance or sociality; status and power; formality; and the specific function of deixis. These factors interacted to shape the use of deixis in Taylor Swift's speech at New York University.